In-silico study of Lebanese herbal compounds against carbapenem-resistant Acinetobacter baumannii proteins - Israa Assaf; Nawal Al Hakawati; Jamilah Borjac (Informatics in Medicine Unlocked, 2023)
Acinetobacter baumannii is one of the main contributors to nosocomial infections. Recently, the prevalence of A. baumannii resistant to carbapenem (CRAB) has grown, further limiting available treatments. Purpose: Given that the antimicrobial effect of medicinal plants has been proven on different pathogenic bacteria, the purpose of this study is to find efficient herbal compounds capable of inhibiting CRAB important proteins, by computational screening. Phytochemicals compounds of seven Lebanese herbs were collected from related articles. CRAB protein structures were obtained from RCSB PDB database. The 3-D structures of phytochemicals were obtained from PubChem and SpiderChem databases. Molecular docking analysis of phytochemicals was performed using ArgusLab 4.0.1 against oxacillinases Ambler Class D proteins including blaoxa-23, blaoxa-24, blaoxa-58, and blaoxa-143, and the Metallo-lactamases Ambler Class B blaNDM-1. Our study showed that the phytochemicals Ursolic and Oleanolic acid, Vebonol, γ & β Tocopherol, Lyoniside, Rosmarinic acid, and 3,4-Dicaffeoylquinic acid had the highest binding energy to the five CRAB proteins (−14.33 to −10.7645 kcal/mol score range), with Ursolic acid and Vebonol having the highest binding affinity to all proteins. Ursolic acid was shown to have no or minimum side effects while Vebonol is known to having carcinogenic effect in rats. Based on our study, Origanum syriacum and Rhus coriaria L. showed to possess the best compounds against CRAB important proteins. These medicinal compounds may be effective as antibiotics against CRAB. Furthermore, computationally based techniques can be reliable for estimating the bioavailability of the phytochemicals that can be used to create innovative medications.